Follow your gut : the enormous impact of tiny microbes - Knight, Rob, (Researcher), ....-; Buhler, Brendan, ....- (New York : Simon & Schuster, 2015)
You are made up of about 10 trillion human cells-- but there are about 100 trillion microbial cells in and on your body. Knight and Buhler examine the links between our microbes and numerous diseases, and show how microbes are integrated into almost all aspects of our lives. Learn how microscopic life inside us influences our health, mood, and more.
The body microbial ; How we get our microbiome ; In sickness and in health ; The gut-brain axis ; A brief history of bugs ; Hacking your microbiome ; Antibiotics ; The future ; The American gut ; The science (and art) of microbiome mapping.
Includes bibliographical references (pages 99-114).
Keywords: Human body -- Microbiology; Microorganisms; Intestines -- Microbiology -- Popular works; Human body -- Microbiology; Microorganisms